2016
DOI: 10.1371/journal.pone.0163589
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Interval Size Estimation Is Associated with Early Musical Training

Abstract: Although pitch is a fundamental attribute of auditory perception, substantial individual differences exist in our ability to perceive differences in pitch. Little is known about how these individual differences in the auditory modality might affect crossmodal processes such as audiovisual perception. In this study, we asked whether individual differences in pitch perception might affect audiovisual perception, as it relates to age of onset and number of years of musical training. Fifty-seven subjects made subj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A number of factors extraneous to fundamental frequency have influence over the perception of relative pitch. For example, the perception of relative pitch can be influenced by pitch register (Russo & Thompson, 2005a), loudness (McDermott, Lehr, & Oxenham, 2008;Thompson, Peter, Olsen, & Stevens, 2012), facial movement (Abel, Li, Russo, Schlaug, & Loui, 2016;Thompson, Graham, & Russo, 2005;Thompson, Russo, & Livingstone, 2010) and brightness (Allen & Oxenham, 2014;McDermott et al, 2008;Russo & Thompson, 2005b). With regard to the latter, note-to-note changes in brightness that are congruent with changes in pitch have been found to lead to an expansion of perceived interval size (i.e., pitch distance), whereas incongruent changes lead to a contraction.…”
mentioning
confidence: 99%
“…A number of factors extraneous to fundamental frequency have influence over the perception of relative pitch. For example, the perception of relative pitch can be influenced by pitch register (Russo & Thompson, 2005a), loudness (McDermott, Lehr, & Oxenham, 2008;Thompson, Peter, Olsen, & Stevens, 2012), facial movement (Abel, Li, Russo, Schlaug, & Loui, 2016;Thompson, Graham, & Russo, 2005;Thompson, Russo, & Livingstone, 2010) and brightness (Allen & Oxenham, 2014;McDermott et al, 2008;Russo & Thompson, 2005b). With regard to the latter, note-to-note changes in brightness that are congruent with changes in pitch have been found to lead to an expansion of perceived interval size (i.e., pitch distance), whereas incongruent changes lead to a contraction.…”
mentioning
confidence: 99%
“…Semantic influences may well explain, for example, why musicians in previous studies have shown increased sensitivity to pitch-height congruency (Eitan & Granot, 2006;Paraskevopoulos et al, 2015), possibly owing to their increased familiarity with musical notation. Indeed, many previous studies have used musical notation or closely resembling visual stimuli; and, not surprisingly, in their familiar domain, musicians have shown increased behavioral benefits compared to nonmusicians (Abel, Li, Russo, Schlaug, & Loui, 2016;Nichols & Grahn, 2016;Paraskevopoulos et al, 2015;Paraskevopoulos et al, 2012). It is indeed plausible that considerable experience with musical notation and terminology results in an association between pitch and vertical position that is quite explicit in musicians, and that this familiarity effect becomes apparent whenever the pitch intervals can actually be represented by musical notation, resulting in musicians' stronger associations between vertical position and pitch as found in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is indeed plausible that considerable experience with musical notation and terminology results in an association between pitch and vertical position that is quite explicit in musicians, and that this familiarity effect becomes apparent whenever the pitch intervals can actually be represented by musical notation, resulting in musicians' stronger associations between vertical position and pitch as found in previous studies. However, owing to the focus on the PoIE, the present study targeted visual influences on responses to near-threshold auditory stimuli (20 and 30 cents deviants) as opposed to musical scale intervals (1+ semitones), where musicians may benefit from their explicit knowledge about pitch intervals and their labels (Abel et al, 2016;Nichols & Grahn, 2016). Therefore, the pitch intervals could not be represented by musical notation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Viewing the performer and reading lyrics can increase their musical enjoyment ( Gfeller et al, 2000 ; Looi and She, 2010 ) and raves targeted at the deaf community frequently include musical visualization. Furthermore, the size of sung musical intervals can be determined when only viewing the singer’s face (without audio), with larger intervals associated with more head movement, eyebrow raising, and mouth opening ( Thompson and Russo, 2007 ; Abel et al, 2016 ). Viewing a singer’s face with accompanying audio can also bias the perception of pitch interval size ( Thompson et al, 2010 ), with the mouth apparently increasing in significance as audio signal-to-noise ratios become more challenging ( Russo et al, 2011 ).…”
Section: Is Haptic Stimulation Suitable For Enhancing Music Perception?mentioning
confidence: 99%